Dualizm w epistemologii nauk o zarządzaniu - Sułkowski, Łukasz (Dualism in the management science epistemology, 2006)
The axis of the epistemological division within management, as well as in some other soft sciences can be the antagonism: the hard orientation (newpositivist, system, functionalist) against the soft orientation (humanistic, interpretativist, hermeneutical). Accepting this dichotomous point of view one can observe that in management sciences takes place the process „of the nodulising” of different schools which are situated on the opposite ends of the described continuum. Thus for example with reference to the strategy of the school: planner, positional and resources schools are based more on “hard” while the evolutional school lies rather on “soft”. The idea research of the influence of the national culture on the management is derived from functionalism, and the perception of the organizational culture as nets of meanings has the interpretativist character. We will find similar partitions in the theory of the management, structures, the conflict and the organizational communication. The foundations of epistemology of management usually hidden, shape the idea and the theory in this sphere.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 13-22